2012
DOI: 10.1038/nm.3024
|View full text |Cite|
|
Sign up to set email alerts
|

Multiphoton imaging reveals a new leukocyte recruitment paradigm in the glomerulus

Abstract: In contrast with many capillary beds, the glomerulus readily supports leukocyte recruitment. However, little is known regarding the actions of leukocytes following their recruitment to glomeruli. We used multiphoton confocal microscopy to examine leukocyte behavior in the glomerular microvasculature. In normal glomeruli, neutrophils and monocytes were retained in capillaries for several minutes, remaining static or migrating intravascularly. Induction of glomerular inflammation resulted in an increase in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
235
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(253 citation statements)
references
References 39 publications
18
235
0
Order By: Relevance
“…Neutrophil-depletion on the other hand prevented platelet accumulation within glomerular capillaries in a model of immune-complex-induced glomerulonephritis (22), emphasising the importance of the interplay between platelets and neutrophils during this disease. Indeed, our unpublished data suggest constitutive on/off interactions between platelets and neutrophils or monocytes in glomerular capillaries (Finsterbusch et al unpublished), leukocyte subsets that both were reported to contribute to renal injury in acute glomerular inflammation (116,117). …”
Section: Platelet-leukocyte Interactions In Pathologic Conditionsmentioning
confidence: 85%
“…Neutrophil-depletion on the other hand prevented platelet accumulation within glomerular capillaries in a model of immune-complex-induced glomerulonephritis (22), emphasising the importance of the interplay between platelets and neutrophils during this disease. Indeed, our unpublished data suggest constitutive on/off interactions between platelets and neutrophils or monocytes in glomerular capillaries (Finsterbusch et al unpublished), leukocyte subsets that both were reported to contribute to renal injury in acute glomerular inflammation (116,117). …”
Section: Platelet-leukocyte Interactions In Pathologic Conditionsmentioning
confidence: 85%
“…Although their regenerative potential is much higher than that of podocytes, chronic exposure of these cells to injurious stimuli in transplantation, for example, immunologic, hypertensive or toxic, likely contributes to glomerulosclerosis (113,114). In vivo imaging studies revealed a novel concept of glomerular inflammation in which leukocytes are retained on the glomerular endothelium for longer periods compared to other vascular beds but do not extravasate (115).…”
Section: The Role Of Glomerular Cellsmentioning
confidence: 99%
“…Mice were kept at 37˚C. Time lapse recordings of GFP + cells in the kidney of Cx 3 cr1 GFP/+ and Cx 3 cr1 GFP/GFP mice were captured using a Leica SP5 mulitphoton microscope system (Leica Microsystems, Mannheim, Germany) with a 320 1.0 NA water immersion objective (18,63). Fluorophores were excited by a SpectraPhysics MaiTai pulsed infrared laser tuned to 860 nm, with emissions captured by nondescanned detectors with 525/50 nm (GFP), 585/40 nm (tetramethylrhodamine isothiocyanate), and 650/50 nm (Alexa 633) filters.…”
Section: Renal Multiphoton Microscopymentioning
confidence: 99%